2014
DOI: 10.1142/s179354581450014x
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy (NIRS) as a useful tool to evaluate the treatment efficacy of positive airways pressure therapy in patients with obstructive sleep apnea syndrome (OSAS): A pilot study

Abstract: In obstructive sleep apnea syndrome (OSA) the periodic reduction or cessation of breathing due to narrowing or occlusion of the upper airway during sleep leads to an impaired cerebral vascular autoregulation that is associated with an increased cardiovascular risk, including stroke. Continuous positive airways pressure (CPAP) therapy at night is the most e®ective treatment for OSA and has been shown to reduce the cardiovascular risk in OSA patients. However, there is no suitable bedside monitoring method evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…In this pilot study, we found that cerebral hemodynamics showed different changing patterns induced by periodic The oscillations in cerebral HbO2, HHb and BV induced by OSA events in this study have been repeated confirmed by previous studies [13][14][15][16][17][18] . All of these studies, reported on a decrease in HbO2 while an increase in HHb during A/H events, and a reverse pattern immediately after the end of the events.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this pilot study, we found that cerebral hemodynamics showed different changing patterns induced by periodic The oscillations in cerebral HbO2, HHb and BV induced by OSA events in this study have been repeated confirmed by previous studies [13][14][15][16][17][18] . All of these studies, reported on a decrease in HbO2 while an increase in HHb during A/H events, and a reverse pattern immediately after the end of the events.…”
Section: Discussionsupporting
confidence: 87%
“…It is a powerful tool to study cerebral hemodynamics during all night sleep 12 . Several studies with NIRS repeatedly reported an impairment of cerebral oxygenation in the patients with sleep apnea [13][14][15][16][17][18] . However, no study has compared cerebral hemodynamics in patients with OSA and PLMS so far.…”
Section: Introductionmentioning
confidence: 99%
“…The NIRS data obtained from brain and muscle were compared in both the time domain and the frequency domain. Several data‐preprocessing steps were performed before the comparisons (Zhang et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Along with the development of methods for processing fNIRS data, [1][2][3] fNIRS has been wildly used in cognitive neuroscience, [4][5][6] disease, 7 infant 8 and hyperscanning studies 9 due to its°exibility and high ecological validity, and obtained signi¯cant results. In studies using Á[HbO2] and Á[Hb] to represent the brain activity, heartbeat is the most dominant physiological noise, and should be¯ltered or removed directly.…”
Section: Introductionmentioning
confidence: 99%